LIPOSUCTION WITH ANALGOSEDATION AND TUMESCENT LOCAL ANESTHESIA VS. GENERAL ANESTHESIA: COMPARATIVE STUDY - Grncharevski M; Rafajlovski G; Kartalov A; Pejkova S; Jovanovski T; Peev I (Department of Anesthesia and Reanimation, Faculty of Medicine, "Ss.Cyril and Methodius", University, Skopje, Macedonia, 2020)
Introduction: Liposuction is one of the most popular cosmetic surgery with unique anesthetic considerations. It may be performed with local tumescent anesthesia and analgosedation, regional or general anesthesia, depending on volume aspirated, region treated and patient’s preference. Objectives: To present our experiences with liposuction on patients using analosedation and local luminescent anesthesia in comparison to general anesthesia. Material and Methods: Study analyzes 40 patients, ASA I-II with a mean age of 39.3 ± 5.6 years that underwent liposuction. All patients were divided in two groups. In the first group we have 20 patients operated with general anesthesia and 20 patients (Group-2) operated with analgosedation and tumescent local anesthesia. Formula for tumescence fluid that we used is modified Klein’s solution, comprising 15 ml 2% lidocaine and 1 ml 1:1000 adrenaline in a 500 ml warmed up saline. Several attributes were analyzed among the groups: gender, age, amount of aspirated fat, postoperative pain, by using VAS score at 5 points-2 hr, 4 hr, 6 hr, 12 hr and 24 hr, cumulative 24 hours morphine consumption after the operation, operative time (minutes) and aspirated fat. Results: There was no statistical significance in age, gender and the amount of the aspirated fat among the groups (Group I-3300 vs. Group II-3550 ml, P=0.02853). Operative time (minutes) was significantly higher in group I (p=0,0005). There were statistically significant differences in VAS scores between the groups I and II at all postoperative time points-2 hr, 4 hr, 6 hr, 12 hr and 24 hr. (P < 0.00001). The cumulative 24 hours morphine consumption after the operation was significantly lower in the Group II (mean = 4.83 ± 1. 31) than the Group I (mean = 12 ± 2.41). This difference was statistically significant (p=0.0001). Conclusion: Analgo-sedation and local tumescent anesthesia is as effective as general anesthesia in terms of amounts of liposuction fat. Allowing patient’s cooperation during intervention this new anesthesia technique decreases patient’s postoperative morphine consumption, operation time and VAS score at all postoperative points.
Keywords: analgosadation; liposuction postoperative pain; tumescent local anesthesia